Pengaruh Penyuluhan Mengenai Dismenore Terhadap Pengetahuan Dan Perilaku Penanganan Dismenore Pada Siswi Sma Muhammadyah 1 Surakarta - Utami, Priyanka G; Raden, Abkar; primadewi, Novi (Nexus Kedokteran Komunitas, 2013)
Objective:To determinethe influence of dysmenorrhea counseling towards SMA Muhammadyah 1 Surakartaâs female studentâs knowledge and handling behaviour toward dysmenorrhea Background:Dysmenorrhea was the most frequent menstrual problem, but women still lack of consideration towards this symptom so that the handling of this symptom was still not enough.Women need to know that the handling of this symptom is depend on knowledge about this symptom causation. Methods:Samples, SMA Muhammadyah 1 Surakartaâs female studentsâ school year of 2011/2012. The number of sample: 53 female students. Sampling technique: purposive random sampling. Before the counseling began, a pretest was held to meassured students knowledge about dysmenorrhea and their handling behaviour to reduceÂ  pain they had felt. After pretest, the counseling about dysmenorrhea; the differences between primary dysmenorrhea and secondary dysmenorrhea; and the management they should do towards certain condition was given. After that, there were question session, quiz session, and tutorial discussion session. Then, they received a post test to meassure wether if there were any level of knowledge and handling behaviour differences between after and before the counseling. Then the data was analyzed usingÂ  paired T test. Results: The result using paired T test showed that the number of significance are 0.00 <0,05 so that it was significance. Level of knowledge before the counseling is lower than after the counseling. The handling behaviours towards dysmenorrhea before and after counseling are also different.The resultshowed that,after the counseling, the number of handling behaviourâs preferences which were warming lower abdominal part, seeking for medical help, and consuming vegetables and fruits were increased. On the other side, the number of handling behaviourâs preferences which were consuming herbal medicine and AINSD (Anti Inflammation Non Steroid Drugs) were decreased. Conclusion:Counseling about dysmenorrhea could influence studentâs level of knowledge and handling behavior towards dysmenorrhea Â  Key words:Counseling, level of knowledge, handling behaviour, dysmenorrhea